The Effectiveness of High School Biology Students Worksheets Based on Critical Thinking Skills on the Protista Concept - Mirna Hariati; Muhammad Zaini; Kaspul Kaspul (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
Learning in the 2013 curriculum has one component, namely the existence of teaching materials in the form of student worksheets. This study aims to describe the effectiveness of student worksheets based on critical thinking skills on the Protista concept. This study uses a formative evaluation design method from Tessmer. The student worksheet developed refers to the student worksheets structure according to Daryanto & Dwicahyono, while his critical thinking skills refer to Facione 1990. Subjects in expert review consist of three experts, subjects in one to one evaluation consist of three students in class X high school and the subjects in the small group evaluation consisted of six high school grade X students. The results of research conducted indicate that: 1) student worksheets have a valid category based on the validity test; 2) student worksheets have a good category based on content practicality tests and has a very good category on practicality expectations based on students' responses; and 3) student worksheets has a very good category based on the assessment of students' critical thinking skills on the effectiveness test and has a very good category on interpersonal skills (working together) and intrapersonal skills (thorough).AbstrakPembelajaran pada kurikulum 2013 memiliki salah satu komponen yaitu adanya bahan ajar berupa Lembar Kerja Peserta Didik (LKPD). Penelitian ini bertujuan untuk mendeskripsikan keefektifan LKPD berbasis keterampilan berpikir kritis pada konsep Protista. Penelitian ini menggunakan metode desain evaluasi formatif dari Tessmer Lembar Kerja Peserta Didik yang dikembangkan mengacu pada struktur LKPD menurut Daryanto & Dwicahyono, sedangkan keterampilan berpikir kritis nya mengacu pada Facione 1990. Subjek pada expert review terdiri atas tiga orang ahli, subjek pada one to one evaluation terdiri atas tiga orang peserta didik kelas X SMA dan subjek pada small group evaluation terdiri atas enam orang peserta didik kelas X SMA. Hasil penelitian yang dilakukan menunjukkan bahwa: 1) LKPD memiliki kategori valid berdasarkan uji validitas; 2) LKPD memiliki kategori baik berdasarkan uji kepraktisan isi dan memiliki kategori sangat baik pada uji kepraktisan harapan berdasarkan respon peserta didik; dan 3) LKPD memiliki kategori sangat baik berdasarkan penilaian keterampilan berpikir kritis peserta didik pada uji keefektifan serta memiliki kategori sangat baik pada keterampilan interpersonal (bekerja sama) dan keterampilan intrapersonal (teliti).